Effects of LED Light Color and Intensity on Feather Pecking and Fear Responses of Layer Breeders in Natural Mating Colony Cages - Haipeng Shi; Baoming Li; Qin Tong; Weichao Zheng; Dan Zeng; Guobin Feng (Animals, 2019)
Natural mating colony cages for layer breeders have become commonplace for layer breeders in China. However, feather pecking (FP) and cannibalism are prominent in this system. The objective of this study was to investigate the effects of four light-emitting diode (LED) light colors (white: WL, red: RL, yellow-orange: YO, blue-green: BG) with two light intensities for each color, on FP, plumage condition, cannibalism, fear, and stress. A total of 32 identical cages were used for the eight treatments (four replicates for each treatment). For both light intensities, hens in RL had a lowest frequency of severe FP, whereas hens in WL had the highest frequency of severe FP. Hens in RL and BG had better plumage conditions than in WL and YO. Compared with RL and BG treatments, hens treated with WL and YO had a significantly longer tonic immobility (TI) duration. Hens treated with RL had a higher concentration of 5-hydroxytryptamine (5-HT), a lower concentration of corticosterone (CORT), and a lower heterophil to lymphocyte ratio than WL and YO. Furthermore, RL could significantly reduce mortality from cannibalism. Overall, hens treated with RL and low light intensity showed a lower frequency of severe FP, less damaged plumage, were less fearful, had lower physiological indicators of stress, and had reduced mortality from cannibalism. Transforming the light color to red or dimming the light could be regarded as an effective method to reduce the risk of FP and alleviate the fear responses of layer breeders.